1991
DOI: 10.1017/s0950268800049268
|View full text |Cite
|
Sign up to set email alerts
|

rDNA fingerprinting as a tool in epidemiological analysis ofSalmonella typhiinfections

Abstract: SUMMARYCharacterization of 169 strains of Salmonella typhi of phage types C1, C4, D1 and D9 isolated in 1975-88 was carried out by rDNA gene restriction pattern analysis.Twenty-four isolates had been recovered during four large waterbone outbreaks in the last 20 years in Sicily; 145 strains, isolated from apparently sporadic cases of infection in Southern Italy in the same period of time, were also examined.Application of rRNA-DNA hybridization technique after digestion of chromosomal DNA with Cla I showed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…Boyd et al (4) investigated the genomic content of a set of isolates: they found such differences that they concluded the genomic reservoir was unstable, even within a highly clonal bacterial population. Several workers using ribotyping with or without PFGE (3,11,12,16,26,27,32) (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Boyd et al (4) investigated the genomic content of a set of isolates: they found such differences that they concluded the genomic reservoir was unstable, even within a highly clonal bacterial population. Several workers using ribotyping with or without PFGE (3,11,12,16,26,27,32) (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Ribotyping was introduced by Grimont & Grimont (1986). It has previously been used to separate biovars of the same species (Moureau et al, 1989;Hernandez et al, 1991;Kiehlbauch et al, 1991) and it has been demonstrated that ribotyping can provide useful epidemiological information concerning Salmonella enterica infections (Martinetti & Altwegg, 1990;Nastasi et al, 1991). Among the restriction enzymes EcoKL, Smal and Hindlll used in this investigation, only EcoKL was able to separate all biovar pullorum isolates from those of biovar galltnarum.…”
Section: Discussionmentioning
confidence: 85%
“…PstI ribotyping is a stable, reproducible, and sensitive method that has been used since 1989 (1,12,18,20,27,28); but it has several limitations: (i) manual ribotyping is technically demanding and automated ribotyping is expensive; (ii) due to the high degree of plasticity of the S. enterica serotype Typhi genome, genetic rearrangements produced by homologous recombinations between rrn operons can occur during the emergence of an outbreak, leading to various ribotypes among outbreak isolates; and (iii) a single genetic rearrangement can substantially modify the banding pattern, precluding an accurate cluster analysis of epidemiologically related isolates (10,21). PstI ribotyping indicated that most of the Vietnamese isolates belonged to the same clonal expansion, confirming the results obtained with the SNP method.…”
Section: Discussionmentioning
confidence: 99%